Pemanfaatan Lahan Tadah Hujan untuk Budidaya Padi Unggul dalam Menghadapi Perubahan Iklim - Rina Kartikawati; Ika Ferry Yunianti; Anicetus Wihardjaka; Prihasto Setyanto (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2017)
Kartikawati et al, 2017.Â Utilization of Rainfed Rice Areas for High Yielding Rice Cultivation on Climate Change. JLSO 6(2):142-149.Many efforts have been conducted by Indonesian government for national food supply and food security through rice cultivation on sub optimal lands in accelerating food sustainability particularly rice, maize and soybean. The rainfed area is an important sub optimal land which should be developed due to 26,5% of Indonesia rice production produced from cultivation system in those area. However, the cultivation in rainfed areas have challenges such as changing of rainfall pattern due to climate change. Therefore, to obtain the information of productivity from high yield rice varieties and methane emission in rainfed area, a study has been conducted by applying innovation of environmental friendly technology such as fertilizer use based on integrated cropping calendar. The study was carried out at Research Station of Indonesian Agriculture Environment Research Institute in Jakenan, which is one of rainfed area in Pati District, Central Java Province. The study was conducted on first growing season (GS 1) or rainy season by applying direct seeded system using rice seeder. Four rice varieties were used for this study, namely Ciherang, Dendang, Inpari 31 and Inpari 24. The study showed that productivity of four rice varieties were 5.92; 7.10; 5.06 and 7.41 t/ha, respectively. Methane emission was significant different among the varieties as 232; 319; 300 and 405 kg/ha/season, respectively.